Shaolin sisters. Vol. 1 - Kakinouchi, Narumi; Smith, Alexander O. (Los Angeles : Tokyopop, 2003)
Julin Kenga always thought that she was an only child and heiress to the Fighting Fang martial-arts clan. So when her kung-fu master gives her a magical bell and tells her to find her two older sisters, it comes as quite a surprise!
Japanese version originally published: Tokyo: Kodansha, 2001.
"100% authentic manga"--Colophon.
"This book is printed 'manga-style' in the authentic Japanese right-to-left format"--Colophon.
Youth age 7+.
Keywords: Sisters -- Juvenile fiction; Martial arts -- Juvenile fiction; Manga; Young adult fiction; Graphic novels